Pengaruh ESG terhadap Cost of Capital selama Pandemi Covid-19 dengan Kinerja Keuangan sebagai Variabel Moderasi (Studi pada Perusahaan SRI-KEHATI Tahun 2020-2023) - Arma Karisma Arditiyan; Agus Purwanto (Politeknik Ganesha Medan, 2025)
This study explores the moderation of financial performance in the relationship between ESG disclosure and the cost of capital in Indonesia during the COVID-19 pandemic. It uses financial data from 15 public companies consistently listed on the SRI-KEHATI stock index from 2020 to 2023. The regression analysis employed is multiple linear regression using the SPSS v28 program. The results reveal that environmental disclosure has a significant negative impact on the cost of capital, while social and governance disclosures do not have a statistically significant effect. Furthermore, financial performance strengthens the negative relationship between environmental disclosure and the cost of capital, strengthens the positive relationship between social disclosure and the cost of capital, but has no impact on governance disclosure. This suggests that ESG can help companies survive or even thrive during the pandemic. This study makes an important contribution to the literature by providing empirical evidence on the moderation of financial performance in the relationship between ESG disclosure and the cost of capital in Indonesia during the COVID-19 pandemic. These findings can serve as a reference for academics and practitioners to understand the importance of ESG for companies in developing countries.